Lectin histochemistry of Kudoa septempunctata genotype ST3-infected muscle of olive flounder (Paralichthys olivaceus) - Kang Jaeyoun; Park Changnam; Jang Yeounghwan; Ahn Meejung; Shin Taekyun (Parasite, 2016)
The localization of carbohydrate terminals in Kudoa septempunctata ST3-infected muscle of olive flounder (Paralichthys olivaceus) was investigated using lectin histochemistry to determine the types of carbohydrate sugar residues expressed in Kudoa spores. Twenty-one lectins were examined, i.e., N-acetylglucosamine (s-WGA, WGA, DSL-II, DSL, LEL, STL), mannose (Con A, LCA, PSA), galactose/N-acetylgalactosamine (RCA12, BSL-I, VVA, DBA, SBA, SJA, Jacalin, PNA, ECL), complex type N-glycans (PHA-E and PHA-L), and fucose (UEA-I). Spores encased by a plasmodial membrane were labeled for the majority of these lectins, with the exception of LCA, PSA, PNA, and PHA-L. Four lectins (RCA 120, BSL-I, DBA, and SJA) belonging to the galactose/N-acetylgalactosamine group, only labeled spores, but not the plasmodial membrane. This is the first confirmation that various sugar residues are present in spores and plasmodial membranes of K. septempunctata ST3.